Toxic Effects of Lead Chloride (PbCl2) on Behavioral, Hematological, and Serum Biochemical Parameters in Labeo rohita - Batool, Moazama; Naz, Saima; Chatha, Ahmad Manan Mustafa; Ain, Qurat Ul; Irshad, Asma; Mahmood , Mamoona; Aziz , Asma; Abbas, Ghulam; Yasmin, Fatima (BioScientific Review, 2024)
Background. Lead (Pb) is an extremely toxic metal in aqueous environments. Fish are highly susceptible to the lethal effects of lead exposure since it induces toxicity in fish, with oxidative stress causing neurotoxicity. Moreover, lead affects immune responses in exposed fish. This study aimed to determine the numerous lethal effects of lead exposure, comprising oxidative stress, immune responses, and neurotoxicity. It also aimed to identify its indicators to assess the degree of lead toxicity. Method. Freshwater fish Labeo rohita, (number of fish = 60), with body weight (70–120 g), were divided into one control and three experimental groups namely T1, T2, and T3 (0.44mg/l, 0.89mg/l, and 1.34 mg/l), randomly. For comparative analysis of changes in hematological and biochemical parameters, samples were collected on 7th, 14th, and 21st day. Results. There was a significant increment in WBC. While, RBCs count, hemoglobin (Hb), and hematocrit were significantly decreased in treated groups as compared to the control group. The mean corpuscular hemoglobin (MHC) and the mean corpuscular hemoglobin concentration (MCHC) indicated a non-significant reduction in lead treated groups as compared to the control. On the other hand, serum biochemical parameters comprising total proteins (TP), albumin, and globulin reduced significantly (p<0.05). Simultaneously, alkaline phosphatase (ALP), alanine aminotransferase (ALT), aspartate aminotransferase (AST), cholesterol, and glucose significantly (p < 0.05) increased in the treated groups compared to control. Conclusion. The study showed that lead chloride exposure can adversely alternate hematological and biochemical parameters in Labeo rohita, even in minor concentrations